Pengaruh LKPD Berbasis STEAM-PjBL Terhadap Keterampilan Argumentasi Peserta didik Dalam Pembelajaran Biologi: Studi Literatur - Fhadilah Rusva Wulan; Fitri Arsih (LP2M UIN Ambon, 2026)
Argumentation skills are one of the key competencies in biology education because they support students’ ability to express their opinions based on scientific evidence. Various studies on the implementation of STEAM-Project-Based Learning (STEAM-PjBL)-based Student Worksheets (LKPD) have been conducted, but the results remain scattered across various scientific publications. This study aims to analyze the effect of STEAM-PjBL-based LKPDs on students’ argumentation skills in biology learning through a Systematic Literature Review (SLR) approach. The research method followed the PRISMA 2020 guidelines by analyzing ten scientific articles that met the inclusion criteria. The results of the study indicate that STEAM-PjBL-based worksheets have a positive impact on students’ argumentation skills. Improvements were observed in the ability to formulate claims, present evidence, provide reasons, and defend arguments based on scientific data. The findings suggest that STEAM-PjBL-based worksheets are an effective teaching resource for supporting active, collaborative biology learning that is oriented toward the development of argumentation skills.